Intellectual Capital Measurement and Company Performance, Any Real Impact? - Noel Singgih Haryo Pradono; Eka Bertuah; Sapto Jumono; Agus Munandar (Enrichment : Journal of Management, 2022)
This study aims to determine the effect of Intellectual Capital measured by VAIC on company performance measured with ROA, ROE and MBV. As many as 19 non-financial companies with 183 observations for the period of 2010-2020 (unbalanced panel) was used for panel data regression model. fixed effect model with robust is the most suitable model for ROA and ROE panel data regression. For MBV random effect model is considered appropriate in this research. According to the results only human capital is the most significant component for ROA and ROE. For MBV, none of the components have significant impact on share performance. Regression result showed that MBV is not suitable to measure company share performance.